Emotional Intelligence, Work Engagement, and Organizational Commitment of Indonesian Army Personnel - Aulia Aulia (ANIMA Indonesian Psychological Journal, 2016)
The aim of this study was to empirically test the relationship between emotional intelligence, work engagement, and organizational commitment Indonesian Army personnels. A quantitative research method was used, utilizing scales of organizational commitment, emotional intelligence, and work engagement. Indonesian Army personnels of KOREM XX, KODIM, YY, and KODIM ZZ were the population of this study. Data analysis using regression techniques revealed an R value of .482 (p < .001). This showed a significant relationship between emotional intelligence, work engagement, and organizational commitment. In addition, partial correlation analysis showed a significant relationship between work engagement and organizational commitment (r = .447 and p < .001), but there was no significant relationship between emotional intelligence and organizational commitment (r = .129 and p > .05). Effective contribution of work engagement on organizational commitment of the Indonesian Army personnel was 23.2%.